2017
DOI: 10.19080/gjo.2017.09.555759
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Linguistic Measures of Toddlers with Repaired Cleft Palate Following Early Intervention Program

Abstract: Maternal involvement plays an important role in early language intervention for children with repaired cleft lip and palate (RCLP) and aids in the development of speech and language. Research to document the usefulness of the same is limited. The present study attempts to provide an insight on the changes in maternal linguistic output by involving mothers in a parent-implemented early intervention program for toddlers with RCLP. The different maternal measures such as the total number of words, utterances, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Pushpavathi et al suggested that mothers' involvement in early language intervention helps in the language development of children with repaired cleft lip and palate. They concluded that home training and stimulation by parents significantly improve the speech and language of children with CLP [36]. Some investigators reported that children with cleft lip and palate show poor cognitive-linguistic and learning abilities than normal children [37].…”
Section: Discussionmentioning
confidence: 99%
“…Pushpavathi et al suggested that mothers' involvement in early language intervention helps in the language development of children with repaired cleft lip and palate. They concluded that home training and stimulation by parents significantly improve the speech and language of children with CLP [36]. Some investigators reported that children with cleft lip and palate show poor cognitive-linguistic and learning abilities than normal children [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concluded that language deficits are related to phonological disorders [18], compensatory articulation [19], parent interaction, and stimulation [20]. Thus, speech and language pathologists should evaluate speech and language development in children with cra-…”
Section: Discussionmentioning
confidence: 99%